Coronary artery disease in patients with cancer: challenges and opportunities for improvement. (September 2021) - Carrillo-Estrada, Montserrat; Bobrowski, David; Carrasco, Rodrigo; Nadler, Michelle B.; Kalra, Sanjog; Thavendiranathan, Paaladinesh; Abdel-Qadir, Husam
Abstract : Purpose of review: Coronary artery disease (CAD) is a common comorbidity in patients with cancer. We review shared risk factors between the two diseases and cancer treatments that increase the risk of CAD. We also discuss outcomes and management considerations of patients with cancer who develop CAD. Recent findings: Several traditional and novel risk factors promote the development of both CAD and cancer. Several cancer treatments further increase the risk of CAD. The presence of cancer is associated with a higher burden of comorbidities and thrombocytopenia, which predisposes patients to higher bleeding risks. Patients with cancer who develop acute coronary syndromes are less likely to receive timely revascularization or appropriate medical therapy, despite evidence showing that receipt of these interventions is associated with substantial benefit. Accordingly, a cancer diagnosis is associated with worse outcomes in patients with CAD. The risk-benefit balance of revascularization is becoming more favorable due to the improving prognosis of many cancers and safer revascularization strategies, including shorter requirements for dual antiplatelet therapy after revascularization. Summary: Several factors increase the complexity of managing CAD in patients with cancer. A multidisciplinary approach is recommended to guide treatment decisions in this high-risk and growing patient group.